Solution‐Processed Bilayer Dielectrics for Flexible Low‐Voltage Organic Field‐Effect Transistors in Pressure‐Sensing Applications. Issue 9 (11th July 2018) - Yin, Zhigang; Yin, Ming‐Jie; Liu, Ziyang; Zhang, Yangxi; Zhang, A. Ping; Zheng, Qingdong
Abstract: Flexible pressure sensors based on organic field‐effect transistors (OFETs) have emerged as promising candidates for electronic‐skin applications. However, it remains a challenge to achieve low operating voltages of hysteresis‐free flexible pressure sensors. Interface engineering of polymer dielectrics is a feasible strategy toward sensitive pressure sensors based on low‐voltage OFETs. Here, a novel type of solution‐processed bilayer dielectrics is developed by combining a thick polyelectrolyte layer of polyacrylic acid (PAA) with a thin poly(methyl methacrylate) (PMMA) layer. This bilayer dielectric can provide a vertical phase separation structure from hydrophilic interface to hydrophobic interface which adjoins well to organic semiconductors, leading to improved stability and remarkably reduced leakage currents. Consequently, OFETs using the PMMA/PAA dielectrics reveal greatly suppressed hysteresis and improved mobility compared to those with a pure PAA dielectric. Using the optimized PMMA/PAA dielectric, flexible OFET‐based pressure sensors that show a record high sensitivity of 56.15 kPa −1 at a low operating voltage of −5 V, a fast response time of less than 20 ms, and good flexibility are further demonstrated. The salient features of high capacitance, good dielectric performance, and excellent reliability of the bilayer dielectrics promise a bright future of flexible sensors based on low‐voltage OFETs for wearable electronic applications. Abstract : Flexible low‐voltage organic field‐effect transistors (OFETs) for pressure‐sensing applications are demonstrated by using solution‐processed poly(methyl methacrylate)/polyacrylic acid dielectrics that achieve greatly enhanced charge transportation with reduced hysteresis. The resulting OFET‐based pressure sensors exhibit a record high sensitivity of 56.15 kPa −1 at a low operating voltage of −5 V, a fast response time of <20 ms, and good flexibility.